Supportive Information DES and Case Study Analysis - Moreno Beguerisse, Mariale; Charnley, Fiona; Court, Richard; Wright, Matt (Cranfield University, 2018)
Supportive information for the full case study analysis and the DES simulation
Keywords: Circular Economy'; 'DES'; 'Re-Distributed Manufacture'; 'Manufacturing Management'